تجديد الفكر التربوى الإسلامي عند الشيخ إمام زركشي (State Islamic University (UIN) of Sunan Ampel Surabaya, 2011)
This paper deals with the idea of reforming an Islamic education in Indonesia through the educational system of pesantren by referring particularly to the thought of Imam Zarkasyi, the founder and leader of Pesantren Gontor. The paper argues that Gontor symbolizes not only the courage of people formerly regarded as educationally marginalized, offering what is best for their fellow country-men, but also the very quality of Islam itself as well as its ability to deal with ever-present social problems. Delving into the depth of Imam Zarkasyi’s thinking, the paper identifies that there are several areas in which he tried his utmost to renew the outlook of his pesantren: (1) the method of Arabic-teaching as a foreign language, (2) the development of pesantren curriculum which integrates both Islamic and non-Islamic sciences, (3) the integration of intra-curricular, extra-curricular, and co-curricular subject-matters, (4) the combination between moral, intellectual, spiritual-religious, and physical education and education in self-management, leadership, and life-skill, (5) managerial base for the endowment system so as to strengthen the institutional aspect of the pesantren. The paper argues that the success of the pesantren lies not only in its ability to produce men of excellence but also its systematic efforts to accumulate wealth.